38‐3: Evaluating Augmented Reality (AR) Eyewear Display Under Ambient Environment. Issue 1 (29th May 2019) - Mou, Xi; Wang, Jianping
Abstract : The augmented reality (AR) display is one of the arising display technologies. An AR display system creates an immersive aspect of the real environment by generating the virtual image with a micro‐display and fusing the external real‐time image into the same scene. Unlike traditional LCDs, the AR display has a very different image formation mechanism that allows its testing method to be different from conventional methods. This paper introduces some of the main issues related to the real‐scene fused with the virtual image under ambient conditions.